2020
DOI: 10.1093/cid/ciaa162
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Reduction in Third-generation Cephalosporin Usage in Adult Inpatients Following Introduction of an Antimicrobial Stewardship Program in a Large, Urban Hospital in Malawi

Abstract: Background Third-generation cephalosporins (3GC) remain the first-choice empiric antibiotic for severe infection in many sub-Saharan African hospitals. In Malawi, the limited availability of alternatives means that strategies to prevent the spread of 3GC resistance are imperative; however, suitable approaches to antimicrobial stewardship (AMS) in low-income settings are not well studied. Methods We introduced an AMS intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
44
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 27 publications
0
44
1
Order By: Relevance
“…It would also be important to incorporate regular reminders about the app into the implementation strategy. A recently published study by Lester et al [ 29 ] highlighted that implementing a locally appropriate, pragmatic antibiotic guideline through an app, supported by a simple educational strategy of weekly ‘reminders’, led to a significant reduction in third generation cephalosporin usage as well as an increase in the proportion of 48-h antibiotic reviews.…”
Section: Discussionmentioning
confidence: 99%
“…It would also be important to incorporate regular reminders about the app into the implementation strategy. A recently published study by Lester et al [ 29 ] highlighted that implementing a locally appropriate, pragmatic antibiotic guideline through an app, supported by a simple educational strategy of weekly ‘reminders’, led to a significant reduction in third generation cephalosporin usage as well as an increase in the proportion of 48-h antibiotic reviews.…”
Section: Discussionmentioning
confidence: 99%
“…In Malawi, lack of alternatives has been reported as a reason for preventing the broad use of 3GCs in most hospitals [ 39 ]. An antimicrobial stewardship program implemented in adult medical wards at QECH was effective in reducing the use of 3GCs [ 40 ]. Such a program should be extended to other departments for promoting the rational use of antibiotics as inappropriate use of 3GCs may facilitate the emergence of multi-drug resistant pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…However, reports regarding efforts to reduce antibiotic usage have mainly focused on interventions for in-hospital prescriptions and injectables. [5][6][7][8][9][15][16][17][18][19]24,25 In addition, no reports are examining the effects of interventions on outpatient prescriptions. This is the first report to evaluate the effects of a revised antibiotic formulary on both in-and out-hospital prescriptions to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Fujibayashi et al reported that revising clinical pathways effectively reduced antibiotic consumption and shortened the antibiotic administration period without increasing the incidence of surgical site infections. 10 Preauthorization and prospective audit and feedback [5][6][7][8][9]24,25 the usage of oral cephalosporins, macrolides and fluoroquinolones to the 50% target. In the future, it is thought that these combined efforts will be necessary at our hospital as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation